Identificação e análise de impactos monetários e não monetários decorrentes da implantação da Cidade Administrativa - Raquel Andreia Franco (2013)
This study aims to evaluate monetary and non-rnonetary impacts related to the implementation of the Cidade Administrativa (CAMG). For this, we conducted an exploratory research, predominantly quantitative, but also qualitative aspects. We used primary data relating to the maintenance costs of the agencies and entities installed in CAMG, to determine whether such a deployment impacted the behavior trend of public spending, and questionnaires to capture the perception of public servants and employees regarding building infrastructure, logistics and technology available in the complex and citizens about the potential impacts related to public services, tourism potential, the government's image and transportation and transit. The research showed that the CAMG may have contributed to the slowdown in expenditure growth taken together, however, there is no default behavior of all items analyzed. That is, some tended to increase, others showed no change or declined. Regarding the perception of public servants and employees, there is, on average, technological improvement at the expense of worsening of such items as noise in the workplace and flooring used, increasing the residence time shift-work and to meetings and spend transportation and food. As for individual productivity, the research allowed this item, on average, did not change when comparing CAMG with previous structures. Regarding the perception of citizens, the data showed that among the options made, the item that most worsened due to the implementation of CAMG was transportation and transit, which was improved over the government's image and that less experienced or what change people do not know how to answer relates to the provision of public services. The study concluded, finally, that it is urgent to foster a culture of development and use of technical feasibility studies and financial public sector to facilitate decision-making on major projects.